A small and efficient dimerization/packaging signal of rat VL30 RNA and its use in murine leukemia virus-VL30-derived vectors for gene transfer. - Torrent, C (1994)
Retroviral genomes consist of two identical RNA molecules associated at their 5' ends by the dimer linkage structure located in the packaging element (Psi or E) necessary for RNA dimerization in vitro and packaging in vivo. In murine leukemia virus (MLV)-derived vectors designed for gene transfer, the Psi + sequence of 600 nucleotides directs the packaging of recombinant RNAs into MLV virions produced by helper cells. By using in vitro RNA dimerization as a screening system, a sequence of rat VL30 RNA located next to the 5' end of the Harvey mouse sarcoma virus genome and as small as 67 nucleotides was found to form stable dimeric RNA. In addition, a purine-rich sequence located at the 5' end of this VL30 RNA seems to be critical for RNA dimerization. When this VL30 element was extended by 107 nucleotides at its 3' end and inserted into an MLV-derived vector lacking MLV Psi +, it directed the efficient encapsidation of recombinant RNAs into MLV virions. Because this VL30 packaging signal is smaller and more efficient in packaging recombinant RNAs than the MLV Psi + and does not contain gag or glyco-gag coding sequences, its use in MLV-derived vectors should render even more unlikely recombinations which could generate replication-competent viruses. Therefore, utilization of the rat VL30 packaging sequence should improve the biological safety of MLV vectors for human gene transfer.